La gentrification des « espaces naturels » en Angleterre : après le front écologique, l’occupation ? - Frédéric Richard (L'Espace Politique)
One feature of the UK, and even more of England, is the high population density and degree of its urbanisation. In this peculiar context, and from different points of view (landscape, functional, land use, symbolic or social), the least artificialized spaces, either rural or natural spaces, represents a very specific value. Reinforced in this way by numbers of protection policies and devices, like the National Parks for instance, rural and natural spaces became some desired and lusted for places, particularly by people looking for their amenities. Some people practise outdoor activities or tourism, which are often socially selective, but others decide to settle and inhabit there, contributing most of the time to the gentrification of the countryside. Relying on the Lake District area, this article aims to focus on the link existing between the concepts of eco frontier on one hand and rural gentrification on the other hand. But it is also assumed that this link would allow a better analysis of the gentrification process and of its local modalities.